2019
DOI: 10.1101/lm.050336.119
|View full text |Cite
|
Sign up to set email alerts
|

Semantic generalization of value-based attentional priority

Abstract: This study aimed to determine whether attentional prioritization of stimuli associated with reward transfers across conceptual knowledge independently of physical features. Participants successively performed two color-word Stroop tasks. In the learning phase, neutral words were associated with high, low, or no monetary reward. In the generalization phase (in which no reward was delivered), synonyms of words previously paired with reward served as Stroop stimuli. Results are consistent with semantic generaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 40 publications
5
18
0
Order By: Relevance
“…At the same time, we do not see the performance benefit on reward-associated ink-color trials observed in Krebs et al (2010), which might be explained by the generally low awareness of the reward contingencies in our study, as further suggested by the relationship between awareness and task performance. In this sense, our findings additionally demonstrate that the spillover effect observed for reward-related words is more likely the consequence of associative learning rather than a peripheral consequence of explicit strategy, consistent with the principle of cross-dimension value-driven attention (Anderson, 2015(Anderson, , 2016Anderson, Laurent, & Yantis, 2011 and the finding that value-based interference can be observed in participants unaware of the reward contingencies (Grégoire & Anderson, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…At the same time, we do not see the performance benefit on reward-associated ink-color trials observed in Krebs et al (2010), which might be explained by the generally low awareness of the reward contingencies in our study, as further suggested by the relationship between awareness and task performance. In this sense, our findings additionally demonstrate that the spillover effect observed for reward-related words is more likely the consequence of associative learning rather than a peripheral consequence of explicit strategy, consistent with the principle of cross-dimension value-driven attention (Anderson, 2015(Anderson, , 2016Anderson, Laurent, & Yantis, 2011 and the finding that value-based interference can be observed in participants unaware of the reward contingencies (Grégoire & Anderson, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…A similar interference effect has been observed in studies where a certain feature of an object was predictive of its reward but this feature was incongruent with the goal of the task, e.g. in many tasks employing the Stroop Effect (Bustamante et al, 2021; Grégoire and Anderson, 2019; Krebs et al, 2013, 2011, 2010).…”
Section: Discussionsupporting
confidence: 68%
“…Semantic generalization of learning has been widely found in fear/aversive conditioning (Boyle et al, 2016;Dunsmoor et al, 2012;Dunsmoor & Murphy, 2014;Grégoire & Greening, 2019;Koban et al, 2018;Lei et al, 2019;Lei et al, 2019;Liu et al, 2019) and was recently also demonstrated for reward learning (Grégoire & Anderson, 2019). Here, we show that semantic generalization can occur without any emotional or motivational factors, suggesting that it is a general associative learning mechanism.…”
Section: Discussionsupporting
confidence: 70%
“…Although the studies discussed above all involved fear/aversive conditioning, a recent study by Grégoire and Anderson (2019) extended the study of semantic generalization to reward learning. In a colour-naming (Stroop) task, two words were each paired with either high, low, or no reward.…”
Section: Semantic-based Associative Learning and Generalizationmentioning
confidence: 99%
See 1 more Smart Citation